Bargaining behavior in insurance markets - Lilo Wagner; Julian Baumann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We rationalize a special type of sharing information which can typically be found in markets for occupational disability insurances. There, firms share information about acceptances and rejections of an applicant. We set up a multiple-step signalling model with uninformed agents and endogenize competing principals' decisions to acquire information on risk types. We formalize the idea that information exchange also serves as a tool to signal an applicant's switching type. This may lessen competition and increase industry profits or result in a higher share of uninsured applicants as compared to a market without information sharing. In any case, consumer welfare is reduced. Our model also helps to understand why access to the system is not made dependent on the provision of own data. In addition, we rationalize the existence of anonymous prequalification tests that allow consumers to gain information about their risk type without risking to enter a system entry.
Keywords: D82; D83; G22; 330